A Phase 2A Trial of the Safety and Tolerability of Increased Dose Rifampicin and Adjunctive Linezolid, With or Without Aspirin, for Human Immunodeficiency Virus–Associated Tuberculous Meningitis: The LASER-TBM Trial. (9th December 2022) - Davis, Angharad G; Wasserman, Sean; Stek, Cari; Maxebengula, Mpumi; Jason Liang, C; Stegmann, Stephani; Koekemoer, Sonya; Jackson, Amanda; Kadernani, Yakub; Bremer, Marise; Daroowala, Remy; Aziz, Saalikha; et al.
Abstract: Background: Drug regimens that include intensified antibiotics alongside effective anti-inflammatory therapies may improve outcomes in tuberculous meningitis (TBM). Safety data on their use in combination and in the context of human immunodeficiency virus (HIV) are needed to inform clinical trial design. Methods: We conducted a phase 2, open-label, parallel-design, randomized, controlled trial to assess the safety of high-dose rifampicin, linezolid, and high-dose aspirin in HIV-associated TBM. Participants were randomized (1.4:1:1) to 3 treatment arms (1, standard of care [SOC]; 2, SOC + additional rifampicin [up to 35 mg/kg/d] + linezolid 1200 mg/d reducing after 28 days to 600 mg/d; 3, as per arm 2 + aspirin 1000 mg/d) for 56 days, when the primary outcome of adverse events of special interest (AESI) or death was assessed. Results: A total of 52 participants with HIV-associated TBM were randomized; 59% had mild disease (British Medical Research Council (MRC) grade 1) vs 39% (grade 2) vs 2% (grade 3). AESI or death occurred in 10 of 16 (63%; arm 3) vs 4 of 14 (29%; arm 2) vs 6 of 20 (30%; arm 1; P = .083). The cumulative proportion of AESI or death (Kaplan–Meier) demonstrated worse outcomes in arm 3 vs arm 1 ( P = .04); however, only 1 event in arm 3 was attributable to aspirin and was mild. There was no difference in efficacy (modified Rankin scale) between arms. Conclusions: High-dose rifampicin and adjunctive linezolid can safely be added to the standard of care in HIV-associated TBM. Larger studies are required to determine whether potential toxicity associated with these interventions, particularly high-dose aspirin, is outweighed by mortality or morbidity benefit. Clinical Trials Registration: NCT03927313. Abstract : In this phase 2A, randomized, controlled trial, we demonstrate that high-dose rifampicin and adjunctive linezolid is safe in adult human immunodeficiency virus–associated tuberculous meningitis. Larger studies are required to evaluate potential toxicity with high-dose aspirin in relation to benefit on morbidity and mortality.